KAJIAN MASYARAKAT MISKIN DI KOTA SEMARANG: SUATU REFLEKSI GAYA HIDUP - Bambang Bambang; Alam Pradita W; Luqman Hakim (Universitas Ahmad Dahlan, 2012)
The problem of poverty is suspected as old as human life itself. While social scientists agree that the main cause of poverty was economic system prevailing in the society, but poverty itself is not the problem that manifested because of only the economic system. In fact, poverty is a manifestation of human interaction that involves virtually all aspects belonging to the human life, so that the problem is not endless.Problems that occur in urban poverty believed to be caused not only by low incomes, but also by the mindset of respondents that made respondents static. This mindset was reflected in a lifestyle that could be seen from the behavior of consumption, investment, use of leisure time and concern for the salvation of the souls of respondents (safety). It was expected to become the foundation to be used in solving the problems faced by the urban poor and what solutions can be given.With SPSS analysis tool that generated tabulation summarizes, arrangement or compilation of data in the form of numeric tables would explain how the characteristics and description from the lifestyle of the urban poor as a real form of the mindset of the respondents. The results of this study indicated that the majority of the urban poor over the age of 51 years and only educated to primary school. Environmental conditions and poor sanitation, inadequate nutrition fulfillment, availability of adequate clothing though limited, the recreation area around the city of Semarang and concern for the salvation of the souls of respondents who still lack was a general overview from the results of analyzes performed.